Windows of optimal development - Anderson, D. I.; Mayo, A. M. (Routledge handbook of talent identification and development in sport, 2017)
The purpose of this chapter is to discuss the potential relevance of the windows of optimal development and vulnerability notions to TID in sport. We start by providing a brief overview of the readiness concept and a more extensive introduction to the critical periods concept in human development. Next, we use these concepts to discuss the potential risks of initiating practice or training either too early or too late for the development of the anatomical, physiological, psychological, and perceptual-motor substrates that underlie complex sport skill acquisition. The intent is to provide an introduction to the windows of optimal development and vulnerability phenomenon, knowing full well that it is not possible to cover the entire breadth and complexity of the phenomenon in the space available. Readers are encouraged to consult recent reviews of the critical periods and readiness concepts for more extensive coverage of the issues raised in the chapter (e.g., Anderson, 2002; Anderson, Magill, & Thouvarecq, 2012; Anderson & Mayo, 2015; Hensch, 2004; Werker & Hensch, 2015).